Lessing yearbook. - American Lessing Society (Detroit Wayne State University Press, 1997)
Annual
English or German.
Imprint varies: 1969-1979, Munchen, M. Huber.
MLA international bibliography of books and articles on the modern languages and literatures (Complete edition)
Vols. for 1969- issued by American Lessing Society.
Keywords: Lessing, Gotthold Ephraim -- 1729-1781